Voluntary stopping of eating and drinking in the age of medical assistance in dying: ethical considerations for physicians - Peter Allatt; Daniel D.M. Kim; Philip Hébert (Palliative Care and Social Practice, 2022)
Since 2016, when medical assistance in dying (MAiD) became legal in Canada, healthcare professionals (HCPs) have become familiar with exploring and acting upon patients’ wishes to hasten death (WTHD). In contrast to MAiD, the literature on the voluntary stopping of eating and drinking (VSED) is very limited and there are no standards of practice or legal guidance to support HCPs. In this article, the legal and ethical literature as regards VSED is critically reviewed and new standards of practice are proposed.